Blocked and chained: Blockchain and the problems of transparency1. Issue 1 (1st February 2019) - Hofman, Darra; Novin, Alamir
ABSTRACT: Blockchain is frequently claimed to be a democratizing technology. However, its relationship to both law and broader democratic institutions remains uncertain. One claim regarding blockchain's democratic potential is that it is radically transparent and can bring such transparency to existing systems of governance. This paper interrogates that claim in three different ways. Firstly, it examines blockchain technology against broader theories of transparency. Secondly, it examines the relationship between transparency and democracy, questioning how blockchain technologies could mediate that relationship. Finally, it examines how blockchain technologies could impact a particular exercise of transparency, freedom of information requests. This paper finds the relationship of transparency itself to democratic ideals is complex, contested and highly context‐dependent; the "democratizing" technological transparency built into blockchains could easily prove undemocratic in application. Blockchain technology cannot meet broader transparency goals without addressing political gatekeepers and the legal, social, and cultural needs that animate those goals.